2014
DOI: 10.1007/s10278-014-9683-2
|View full text |Cite
|
Sign up to set email alerts
|

Digitized Whole Slides for Breast Pathology Interpretation: Current Practices and Perceptions

Abstract: Digital whole slide imaging (WSI) is an emerging technology for pathology interpretation; however, little is known about pathologists' practice patterns or perceptions regarding WSI. A national sample (N = 252) of pathologists from New Hampshire, Vermont, Washington, Oregon, Arizona, Alaska, Maine, and Minnesota were surveyed in this cross-sectional study (2011-2013). The survey included questions on pathologists' experience, WSI practice patterns, and perceptions using a six-point Likert scale. Agreement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Only a fraction of pathology practices digitize their slides (Onega et al, 2014). Even if digital images were more widely available, there are two key challenges to computerized analysis of whole-slide pathology images (WSI).…”
Section: Introductionmentioning
confidence: 99%
“…Only a fraction of pathology practices digitize their slides (Onega et al, 2014). Even if digital images were more widely available, there are two key challenges to computerized analysis of whole-slide pathology images (WSI).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that accuracy was slightly higher when pathologists used glass slides, as the current study did, compared to digital whole slide imaging (WSI), an emerging technology for pathology interpretation. 18,23 Although currently understudied, intra-observer variability also has the potential to be greater using WSI.…”
Section: Discussionmentioning
confidence: 99%
“…Other aspects of identification and recruitment have been previously reported. 18 Demographic data, practice characteristics, and interpretive experience of the pathologists were queried using a web-based survey. 13,18 …”
Section: Methodsmentioning
confidence: 99%
“…Details of their identification and recruitment have been described elsewhere 10 14. Participating pathologists completed a web-based survey followed by interpreting their assigned test set of 60 cases.…”
Section: Methodsmentioning
confidence: 99%